Book Review of "Character Strengths Interventions: A Field Guide for Practitioners" - Bezanson, Birdie J. (Canadian Journal of Counselling and Psychotherapy, 2018)
Character Strengths Interventions: A Field Guide for Practitioners is a clinical handbook that provides a solid conceptual foundation in strengths-based practice in positive psychology. An authority in the field, Dr. Ryan Niemiec guides the reader through the basic concepts, specific challenges, and the actual implementation of a plethora of strategies into clinical practice. Niemiec encourages practitioners to develop simple practices to build a true positive psychology approach to life. His practice is firmly situated in research with applications that practitioners can readily apply. Niemiec provided a guidebook that will be dog-eared by both novice and seasoned practitioners.